Land Politics in the Ethiopian-Eritrean Border Area between Emperor Yoḥannǝs IV and Mǝnilǝk II - Taddia, Irma (Aethiopica, 2009)
The complex issue of the land tenure system in 19th and 20th century Ethiopia–Eritrea has a tridimensional aspect that constitutes the basis of my reflection here: the native conception of land, the imperial Ethiopian policy and the colonial intervention. A correct evaluation of this interrelation can be properly understood by focusing on a corpus of integrated sources related to local written documentation, oral records and colonial reports. The control of the northern border by Emperors Yoḥannǝs and Mǝnilǝk created various historical problems and a debate focusing on independence and the maintenance of a political autonomy of the Märäb Mǝllaš. Land tenure system is the key factor for understanding the dynamic of power relations in the area at the eve of colonial rule.